A STUDY OF THE CONDITIONS CREATED BY SCHOOLS IN AND OUTSIDE THE CLASSROOM FOR PROMOTING CIVIC SENSIBILITY AMONG SECONDARY SCHOOL STUDENTS IN THE DISTRICT OF CHITRAL, PAKISTAN - Mr. Sher Afzal; Dr. Takbir Ali (International Journal of Contemporary Issues in Social Sciences, 2024)
This paper reports on the findings from a qualitative study regarding the conditions created by schools in and outside the classroom for promoting civic sensibility among secondary school students in the district of Chitral, in KP, Pakistan. Data were collected from four schools through interviews, observations, FGD, and content analysis of the textbooks of Pakistan studies at the secondary level. Data was collected through purposive sampling from eight social studies teachers, four head teachers, and forty students from two private and two public schools in the district of Chitral KP, Pakistan. The findings of the study revealed a mismatch between the textbooks of Pakistan studies and the standards of civic education identified by the civics education curriculum 2009. Moreover, the study explored the best initiatives taken by the private school system for promoting civic sensibility among the students was providing a clean and conducive environment in the schools. The best classroom practices of teachers for promoting civic sensibility in the private school system were ensuring students’ civic activities through debate, and project work, encouraging students to voluntary work in the community, practicing election, and providing a democratic attitude in the classroom. In contrast, the public school system teachers’ initiatives and practices were not favorable to promote civic sense among the students. The teachers’ hurdles in promoting civic sense among the students in public schools were overcrowded classrooms, unavailability of resources in schools, and a less attractive school environment. Simultaneously, the unavailability of trained teachers and no appraisal system was the hurdle in public schools. The study recommends reviewing the textbooks of Pakistan studies by adding the theme of civics which focuses on social values and civic-mindedness. Public schools can promote civic sense among the students by creating a democratic classroom environment involving students in classroom discussions, debates, and project work related to civic sensibility.